Formulation and Characterization of Nanostructured Lipid Carrier Encapsulated Zingiber Zerumbet Oil using Ultrasonication Technique - Hasham, R.; Rosli, N. A.; Abdul Aziz, A.; Aziz, R. (Journal of Advanced Research in Applied Mechanics, 2020)
This study presents the formulation of nanostructured lipid carrier encapsulated Zingiber zerumbet oil (NLC-ZZ) using ultrasonication technique. NLC is the blend of solid lipid, liquid lipid and surfactant for encapsulation of poor water soluble actives. The NLC-ZZ formulation was characterized with respect to particle size, polydispersity index (PDI), zeta-potential, encapsulation efficiency and physical morphology. The NLC-ZZ formulation had an average diameter of 96.59 nm, PDI of 0.192, zeta-potential of -39.88 mV, and encapsulation efficiency of 90%, respectively. The NLC formulation for Zingiber zerumbet oil encapsulation has been successfully developed and is suitable for transdermal delivery system due to their nano-size and stability.